Optimization of Bioslurry-Available Plant Nutrients Using T. brownii and Acanthaceae spp. Biocatalysts - Bakari A. Chaka; Aloys M. Osano; Justin K. Maghanga; Martin M. Magu (Advances in Agriculture)
The plant extracts of T. brownii and Acanthaceae spp. have been used as biocatalysts by several communities in Kenya to hasten anaerobic digestion. This study aimed at assessing the viability of these two extracts in hastening the availability of plant nutrients from bioslurry at ambient conditions. A controlled research design was followed using uncooked kitchen waste as the substrate for 28 retention days. Changes in bioslurry physicochemical properties and available plant nutrients were monitored every 7 days using wet chemistry and spectroscopic methods. The findings indicated that the two extracts significantly impacted the levels of available plant nutrients in the bioslurry compared to the control samples. T. brownii additives significantly increased the levels of lime content, total Kjeldahl nitrogen, total phosphorus, phosphoric acid, sulfur, and soluble silicic acid. On the contrary, Acanthaceae spp. additives significantly increased the levels of calcium, potassium, nitrates, total ammoniacal nitrogen, sulfates, and phosphates in the bioslurry samples. The use of these plant extracts thus reduces the time taken while increasing the concentration of available plant nutrients from bioslurry.